CONCEPT AND PROVERB CONCEPT RELATIONSHIPS IN COGNITIVE LINGUISTICS (Scientific journal of the Fergana State University, 2024)
The article talks about cognitology and its subjects of study, cognitive activity and its connection with linguistics. The most basic studied term in cognitive linguistics is the concept and its basis of paremiues, the study of the paremiological system attracts the attention of experts of semiotics and cognitive sciences, because paremiues are the laws of oral communication, the laws of acquiring, strengthening and using knowledge. It is believed that it provides valuable material for learning.